Identification of the OGLE Blazars behind the Large and Small Magellanic Clouds - Natalia Żywucka; Arti Goyal; Marek Jamrozy; Łukasz Stawarz; Michał Ostrowski; Szymon Kozłowski; Andrzej Udalski (Galaxies, 2017)
We report the selection of blazar candidates behind the Large and Small Magellanic Clouds. Both flat spectrum radio quasar and BL Lacreate objects were selected based on the long-term, multi-colour Optical Gravitational Lensing Experiment photometric data. We cross-correlated the Magellanic Quasar Survey catalogue of spectroscopically confirmed quasars and quasar candidates located behind the Magellanic Clouds with the radio data at six frequencies from 0.8 to 20 GHz. Among the 1654 objects visible in optical range, we identified a sample of 44 newly selected blazar candidates, including 27 flat spectrum radio quasars and 17 BL Lacs. We examined selected objects with respect to their radio, optical, and mid-infrared properties.